Peningkatan pengetahuan pola hidup bersih dan sehat (PHBS) anak-anak panti asuhan Ashabul Kahfi Deli Serdang melalui pendidikan kesehatan berbasis audiovisual - Siregar, Ameilia Zuliyanti; Salsabil, Muhamad Ainun; Zahra, Maitsa Mutiara; Zebua, Sariyanti Magdalena; Jevera, Kezia; Samosir, Novita (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
This study aims to increase knowledge and awareness about clean and healthy living behavior (CHLB) at Ashabul Kahfi orphanage, Deli Serdang Regency. Team 3 of Module Nusantara students from the University of Sumatera Utara conducted health education through audiovisual-based lecture, discussion, and demonstration methods. Respondents consisted of 14 children of various ages (8-14 yearsold) and education levels (kindergarden, primary school, secondary school). The activity included a pretest and posttest to measure the children's knowledge improvement. Results showed a significant increase from the pretest mean score of 56.25 to 81.25 in the posttest, signaling the success of the educational methods used. In conclusion, this program is effective in increasing the understanding and awareness of Ashabul Kahfi orphanage children about PHBS as well as completing the required health infrastructure.